Free vibrations of laminate plates with viscoelastic layers using the refined zig-zag theory – Part 1. Theoretical background. (15th December 2021) - Lewandowski, Roman; Litewka, Przemysław; Wielentejczyk, Przemysław
Highlights: Pioneer application of refined zig-zag theory in dynamic analysis of laminate plates. Separate fractional Zener material description for volumetric and deviatoric strains. Derivation of efficient finite element formulation leading to the non-linear eigen-value problem. Abstract: The refined zig-zag theory is used to solve the dynamic problems for composite sandwich plates made from the elastic and the viscoelastic (VE) layers. The linear constitutive relations are used to model physical properties of the VE layers separately for volumetric and deviatoric strains. The fractional Zener model is used in the formulation of VE material. The Laplace transformation and the finite element method are used to derive the discretized nonlinear eigenvalue problem. The required dynamic characteristics of the plates – the frequency and the damping ratio, fundamental in design of structural elements in many fields of engineering, can be obtained using the procedure described in the companion paper Litewka P. Lewandowski R, Wielentejczyk P. Free vibrations of laminate plates with viscoelastic layers using the refined zig-zag theory – Part 2. Numerical analysis .